“Mestra na essência da palavra” : trajetória docente de Ofenísia Soares Freire (1941 - 1966) - Souza, Renilfran Cardoso de (2017)
The present research had the purpose of investigating the life trajectory of Ofenísia Soares Freire, highlighting the paths of his educational formation and his educational practices in Atheneu Sergipense (1941-1966), as well as to analyze his involvement in the Brazilian Communist Party (PCB) And how this reflected in the teaching career. The theoretical - methodological procedure adopted is linked to Cultural History. In this sense, the main categories of analysis are: biographical approach (2006); social capital, cultural capital, symbolic capital of Pierre Bourdieu (2004, 2007); and the document concept of Jacques Le Goff (1990). We use documentary sources located in the CEMAS - Center of Education and Memory of the Atheneu Sergipense (Cadernets, Correspondences, Student Arcadia, Press, Records, Books of Records, Library of Epiphany Dória (Official Journal and Journal reason), IHGSE - Historical and Geographic Institute of Sergipe (Sergipe Journal, Correio de Aracaju Journal, Official Diary, Decrees), Personal collection of the family of Ofenísia Soares Freire (Curriculum, photographs, decree), Sergipana Academy of Letters (Discourses, publications in magazines). We also refer to the oral sources through the reports of his former students and people from his conviviality. Ofenísia Soares Freire was born in Estância-SE in December of 1913. She moved to Aracaju to study at the Nossa Senhora Sant'Anna School. After completing his studies in primary school, she entered the Rui Barbosa Normal School, concluding in 1930. She taught in some schools in Aracaju and ended her teaching career at Atheneu Sergipense in 1966, when she retired. Thus, the study highlights the performance of Ofenísia Soares Freire in the educational scenario of Sergipe and its contributions to the History of Education.